Attempted Determination of the Structures of Complex Aliphatic Copolyesters. Issue 22 (29th September 2017) - Li, Shanshan; Shen, Jialong; Nichol, Jessica L.; Tonelli, Alan E.
Abstract: Attempts at the microstructural characterization of biodegradable aliphatic polyesters made via melt‐polymerization of three distinct diacids or diesters and three structurally distinct diols are described. Probes sensitive to local, short‐range microstructures ( 13 C‐NMR) and potentially sensitive to overall, global, complete polymer architectures (Kerr effect) are employed. Solution 13 C‐NMR reveals the copolyesters possess largely random comonomer sequences, without, however, complete elucidation of even their shortest comonomer sequences. The limited structural sensitivity of NMR prevents development of meaningful structure–property relations. Observed Kerr effects, on the other hand, clearly demonstrate sensitivity to the presence of distinct microstructures of longer range than are observed by 13 C‐NMR. To identify the details of these longer‐range structural elements, will, however, require the ability to estimate the Kerr constants of these aliphatic copolyesters when they are assumed not only to possess the types and amounts of short‐range microstructures identified experimentally by 13 C‐NMR, but which are located at different positions along their chains. This ambitious goal requires extensive experimental and calculational efforts, which are currently just beginning and will be described subsequently. Abstract : Attempts to use the Kerr effect are discussed, which is sensitive to overall global and complete polymer architectures, to elucidate longer‐range microstructures of complex aliphatic copolyesters beyond those local, short‐range comonomer sequences observable by 13 C‐NMR.